John Chrysostom on Divine Pedagogy: The Coherence of His Theology and Preaching, by David Rylaarsdam - Sabo, Theodore (Religious studies and theology, 2016)
John Chrysostom on Divine Pedagogy: The Coherence of His Theology and Preaching, by David Rylaarsdam. Oxford University Press, 2014. 317 + xxvi pp. Hb., $93.92. ISBN-13: 9780198715382.